Vortex shedding frequency in open-channel lateral cavity. (10th June 2020) - Perrot-Minot, C.; Mignot, E.; Perkins, R.; Lopez, D.; Riviere, N.
Abstract : Abstract : This article aims at predicting the oscillation frequency of open-channel lateral cavities, which are common sheltered zones of riverine environments, and have important ecological impact. Using a theoretical analysis based on an existing model for acoustic cavities and a free-surface lateral cavity experiment, we show that the vortex shedding in the mixing layer between the cavity and the open channel is always constrained by gravity waves even for low Froude numbers ( $F<0.6$ ). This expands previous results from the literature showing the impact of gravity waves on the vortex shedding frequency for high Froude number ( $F>0.6$ ). Measurements of the free-surface oscillation and transverse velocity oscillation frequencies reveal a unique frequency along the mixing layer, equal to the free-surface oscillation frequency anywhere in the cavity. Hence, it is shown that the vortex shedding frequency in an open-channel lateral cavity always equals a match between a natural frequency of the cavity and a solution of the feedback model developed herein for low to moderate Froude numbers.